Особливості розробки інформаційних технологій моделювання туристичних комплексів - Шевчук, С. Ф.; Артеменко, О. І.; Гаць, Б. М. (НТУ "ХПІ", 2014)
Запропонована структура інформаційних технологій для моделювання та аналізу процесів формування і розвитку окремих туристичних об’єктів, цілісних туристичних комплексів на регіональному та локальному рівнях. Розроблені інформаційні технології дають змогу проводити аналіз процесів започаткування та ведення туристичного бізнесу, використання природних та рекреаційних ресурсів відповідної території.

In this paper the structure of information technologies for simulation and analysis of formation and development for integrated tourist complexes at the regional and local areas was developed. Developed information technologies are useful in analysis of the processes in tourist business, effective usage of natural and recreational resources of the area, providing the possibilities of forming evidence-based strategies for the development of regional tourism infrastructure.
Aspects of the development information technologies for simulation of tourist complexes
Keywords: бізнес туристичний; ресурси рекреаційні; ресурси природні; ефективність; information technology; tourist complex; tourist business; natural resources; recreational resources